2019
DOI: 10.3390/su11195302
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Sustainability and Its Performance Implications: An Empirical Analysis in Spanish Public Universities

Abstract: This paper contributes to the literature about sustainability assessment and goes a step further by studying the effect on university performance. The aim is to analyze, from an external perspective, the relationships between the three dimensions of sustainability in universities (environmental, economic, and social), the similarities between universities, and the impact that it can have on performance. In order to carry out an empirical assessment for Spanish public universities, an index is proposed to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 36 publications
(58 reference statements)
3
26
0
Order By: Relevance
“…Also, the environmental pillar is the more addressed, neglecting the social and economic pillars. These results are in accordance with [74], who also found in a study conducted in Spanish Universities that more attention is given to the environmental pillar and that is still necessary to achieve an integrated perspective of sustainability in universities. Those results justify the maximum ranking of only 36% of the tools in the criterion of coverage of sustainability implementation dimension and the same percentage in the criterion of measuring the progress of sustainability implementation in HEIs (see Table 3).…”
Section: Tools Assessmentsupporting
confidence: 91%
See 1 more Smart Citation
“…Also, the environmental pillar is the more addressed, neglecting the social and economic pillars. These results are in accordance with [74], who also found in a study conducted in Spanish Universities that more attention is given to the environmental pillar and that is still necessary to achieve an integrated perspective of sustainability in universities. Those results justify the maximum ranking of only 36% of the tools in the criterion of coverage of sustainability implementation dimension and the same percentage in the criterion of measuring the progress of sustainability implementation in HEIs (see Table 3).…”
Section: Tools Assessmentsupporting
confidence: 91%
“…GM tool was also overall well classified, besides worst classification in terms of Participation and Progress Over Time criteria but has been also widely used since is free, easy to fill and good as a benchmark between universities worldwide, as stressed by many other authors (e.g., [16,49,74]). As Lauder et al [49] stressed under scientific analysis, no ranking can be free from at least some limitations, resulting in unavoidable practical considerations, such as the need for the ranking to be at a level of complexity that can appeal to a wide audience.…”
Section: Tools Assessmentmentioning
confidence: 95%
“…Earlier research analysing plans and reports from 2005 and 2014 showed that Portuguese universities' autonomy and social responsibility led them to develop several timely initiatives and policies towards ESD (a bottom-up approach) and examples of practices for sustainability implementation were found (Farinha et al, 2019). Blasco et al (2019), in a study that was carried out in 40 per cent of public universities in Spain between 2014 and 2016, concluded that including sustainability practices in strategic planning can enhance academic and research performance.…”
Section: Introductionmentioning
confidence: 99%
“…The national cases, e.g. Spanish [12] are particularly informative from the point of view of adaptation for Ukrainian universities. In [13] authors develop a process framework for including education for sustainable development into quality management systems in higher education.…”
Section: Literature Reviewmentioning
confidence: 99%